A nonconventional method for drying of Pseudomonas aeruginosa and its comparison with conventional methods. Issue 7 (19th May 2019) - Umashankar, K.; Chandralekha, A.; Dandavate, Tanmayee; Tavanandi, Hrishikesh A.; Raghavarao, K. S. M. S.
Abstract: In this study, preparation of dried cultures of Pseudomonas aeruginosa using nonconventional drying method, namely, low-temperature low-humidity (LTLH) drying was investigated. The effect of carrier materials (whey protein, corn starch, and trehalose) was examined one at a time and also in combinations (to explore the synergistic effect). The results were compared with those obtained using spray drying and freeze drying in terms of cell survival and dry cell powder yield. The powder samples were analyzed also for morphology, flowability, particle size, and moisture content. In LTLH drying, good cell survival was observed along with high powder yield when compared with that in spray drying. Corn starch showed the highest cell survival (91%) and powder yield (94%, w/w) among the carrier materials employed besides resulting in good cell survival (65%) even after a storage period of 6 months.